SCREENING OF BACTERIAL SYMBIONTS OF SEAGRASS Enhalus sp. AGAINST BIOFILM-FORMING BACTERIA - Bintang Marhaeni; Ocky Karna Radjasa; Dietrich G Bengen; Richardus F Kaswadji (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Seagrasses have been known to produce secondary metabolites that have important ecological roles, including preventing from pathogen infections and fouling organisms. A research aimed at screening the potential of bacterial symbionts of seagrass Enhalus sp. was performed. Bacterial symbionts including endophytes and epiphytes were isolated from the seagrass, and marine biofilm-forming bacteria were isolated from the fiber and wooden panels from the surrounding colonies. A total of 17 epiphyte and 6 endophyte isolates were obtained, however more biological activity was found among endophytes (100%) compared to epiphytes (47%) against biofilm-forming bacteria. In addition, bacterial endophytes inhibited more biofilm-forming bacteria than epiphytes. Interestingly more isolates were obtained from rough surfaces both from fiber and wooden panels than smoothe surfaces. Bacterial symbionts of seagrass Enhalus sp., in particular its endophytes show potential source as natural marine antifoulants.